The Income and Feasibility Analysis of the Corn Farming in Central Buton District - Nikoyan, Anas (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2020)
This study aimed to determine the income and feasibility of corn farming in Central Buton District. The study was conducted in Central Buton District in March - April 2020. The population of the study was the corn farmers in Central Buton District, amounting to 53 people. The determination of the sample used census method by taking the entire population as the research sample. Research data collection was done through direct interviews with respondents using a questionnaire. Research variables include variable costs, fixed costs, total costs, prices, production, and revenues. The analysis of the data used was income analysis and R/C Ratio analysis. The results showed that the income of corn farming in Central Buton District was IDR1,251,453/season, while the coefficient on the R/C ratio was 6, meaning that corn farming in Central Buton District was financially feasible to be developed.